Performa Produksi Ayam Ras Petelur Isa Brown yang Diberi Pakan Jadi dan Campur - Amoi L. Sipayung; Muhammad J. Wattiheluw; Ch. W. Patty (Syntax Corporation Indonesia, 2024)
The study aims to determine the production performance of Isa Brown laying hens who are given finished feed and mixed feed. Research materials include finished feed for laying hens 524AX produced by PT. Charoen Pokphand Indonesia, and mixed feed consisting of a special layer concentrate super 36 SPR added yellow corn and bran. The study was conducted for 4 weeks in Suruhwadang Village, Kademangan District, Blitar Regency. The method used in the study was a survey and observation with the number of samples taken as many as 180 laying hens Isa Brown aged 44 weeks. The variables observed in the study were feed consumption, hen day production (HDP) and feed conversion (Feed Conversion Ratio). The data were analyzed using quantitative descriptive analysis and the test conducted was a t-test of 2 samples using SPSS software version 2.6 to compare production performance given finished feed and mixed feed. The results showed the performance of finished feed production for feed consumption: 113gr/head/day; HDP: 86.50%; FCR: 2.09. While laying hens are given mixed feed as follows: feed consumption: 112.47gr / head / day; HDP: 83.80% FCR: 2.11. The variable results of feed consumption and FCR from finished feed and mixed feed did not differ markedly while HDP from finished feed and mixed feed differed markedly. The conclusion of the results of the study is that Isa Brown laying hens that are given finished feed have more advantages than nutritional content compared to mixed feed, such as amino acids. The finished feed has a crumble shape that is preferred by livestock compared to mixed feed l finer than crumble. This leads to a little more feed consumption than mixed feed.